Relationship between open- and closed-chain eccentric strength measurements in alpine skiers - Impellizzeri, F.; Rampinini, E.; Mognoni, P.; Maffluletti, N.; Schonhubert, H.; Panzeri, A.; Sassi, A. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Alpine skiing performance requires eccentric muscular contractions to resist the gravity and the centrifugal force during the turning phases or to absorb the irregularities of the terrain. For this reason, the measure of eccentric strength is highly relevant in alpine skiers. Isokinetic open-chain tests are traditionally used to measure the eccentric strength. However, the open-chain muscular actions required by these tests are different compared to the closed-chain nature of actual ski performance. To verify if the use of open-chain isokinetic tests can be an acceptable alternative to closed-chain measurements, we examined the relationship between the eccentric strength assessed using an open-chain isokinetic dynamometer and a motorized leg press.